The Effect of the Harezmi Education Model on Secondary School Students’ Science Academic Achievement - Ayşenur Zeybek; Sema İrem Orhan; Abdullah Aydın (Center for Open Science, 2024)
Today, as technology develops, needs also diversify. These emerging needs are tried to be met with changing curriculum, teaching materials and different education models. The Harezmi Education Model (HEM), which has become widespread in Türkiye in recent years, can also be considered because of this process. This study aims to investigate the effectiveness of the HEM on students’ academic achievement. The research was conducted in the first semester of the 2022-2023 academic year with 19 students studying in the 5th and 6th grades of a public secondary school in Türkiye. The research was conducted using a pre-test post-test quasi-experimental design without a control group. Because of the data analysis, it was seen that the courses supported by HEM significantly increased the students’ achievement. Since participants were selected based on volunteering and a 10-week application period was required, the study did not include a control group. Based on this, science teachers are recommended to use HEM more frequently in their lessons in addition to existing teaching.
Keywords: Education; 4. Education